Is BMI a relevant marker of fat mass in 4 year old children? Results from the MINISTOP trial. Issue 11 (November 2018) - Delisle Nyström, Christine; Henriksson, Pontus; Ek, Anna; Henriksson, Hanna; Ortega, Francisco; Ruiz, Jonatan; Löf, Marie
Abstract Background/objectives Due to the increase in childhood obesity, identifying children with excess body fat as early as possible is essential. Body mass index (BMI) is commonly used as a marker of body fat in children, adolescents, and adults, yet whether BMI is a valid marker of body fat in pre-school aged children remains to be confirmed. Therefore, we analyzed the associations of BMI with fat and fat-free mass in healthy 4-year-old Swedish children. Subjects/methods The study comprised of 303 children (135 girls) participating in the MINISTOP obesity prevention trial. Fat and fat-free mass were measured using air displacement plethysmography and we computed fat mass index (FMI) and fat free mass index (FFMI) as fat and fat free mass (kg)/height2 (m). Results BMI was positively yet weakly associated with percent fat mass (boys:r 2  = 0.120, P  < 0.001 and girls:r 2  = 0.224, P  < 0.001). There was a strong association between BMI and the FMI (boys:r 2  = 0.468, P  < 0.001 and girlsr 2  = 0.598, P  < 0.001) as well as between BMI and the FFMI (boys:r 2  = 0.621, P  < 0.001 and girls:r 2  = 0.499, P  < 0.001). Children classified as normal weight had a wide range of percent fat mass (12.3 to 35.3%) and FMI (1.75 to 5.78 kg/m2 ). Conclusions BMI was strongly associated to both FMI and FFMI. Therefore, caution is needed when interpreting body fat status based on BMI values in pre-school children.